If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/3)*(x-4) = 4*x-(3*(x-1))+5/3 // - 4*x-(3*(x-1))+5/3
(1/3)*(x-4)+3*(x-1)-(4*x)-(5/3) = 0
(1/3)*(x-4)+3*(x-1)-4*x-5/3 = 0
1/3*(x-4)+3*(x-1)-4*x-5/3 = 0
(1/3*3*(x-4))/3+(3^2*(x-1))/3+(-4*3*x)/3-5/3 = 0
1/3*3*(x-4)+3^2*(x-1)-4*3*x-5 = 0
10*x-12*x-13-5 = 0
-2*x-13-5 = 0
-2*x-18 = 0
(-2*x-18)/3 = 0
(-2*x-18)/3 = 0 // * 3
-2*x-18 = 0
-2*x-18 = 0 // + 18
-2*x = 18 // : -2
x = 18/(-2)
x = -9
x = -9
| 28x-47=47+28 | | 5=4x+27/3 | | 11/1/3 | | t^2+14t-49=0 | | 5+1/3n=6 | | P=a-b-7 | | 4/5/6/7 | | 5-x/8+3-2x/4 | | -5/3x=35 | | -w+9=-18w-18 | | xsquare+2x-143=0 | | 800=-100x | | 3i/8+8i | | 0.30x+0.05(4-x)=0.10(-28) | | 25x^2-40x-34=0 | | 0.65x+0.05(14-x)=0.10(-5) | | 4/5k-(k+1/2)=1/10(k+1) | | Qd=30-2P | | x+(x+14)+(x+43)=180 | | x+(x+10)+(x+65)=180 | | 11b-18b=84 | | -7y+2(y+6)=2 | | -4x^2+6x+2=0 | | 157=109-w | | f=jr | | -3(y-3y)+6=-2(6y-y)+4+15y | | 11x^2+66x-309=0 | | x+x+1+1/4=5+3/4 | | 3y/4-5=y/2+4 | | 1/9(18y+27)-5=-1/5(5y-20) | | 41=x+(x+3)+(x+8) | | y^2-8=0 |